Pengaruh Kecemasan Berkomputer (Computer Anxiety) Dan Sikap Komputer (Computer Attitude) terhadap Penggunaan Komputer di Kalangan Pendidik - Chinmi Adin Nugraha, Filipus; Viona, Elsa (Yayasan Sembilan Pemuda Indonesia, 2021)
This study aims to determine the factors that influence the use of computers among educators. The sample used was 71 respondents from educators at SD Xaverius 1 Palembang and SMP Xaverius 6 Palembang with non-probability sampling. The data analysis technique used is multiple linear regression analysis. The results showed that the variables fear, anticipation, and pessimism did not have a significant effect on computer use among educators. The optimism variable (optimism) affects the use of computers among educators. The four variables, namely the variables of anxiety (fear), anticipation, pessimism, and optimism together have an effect on computer use among educators